2010
DOI: 10.3109/02770903.2010.481339
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Rhinosinusitis in Allergic Asthmatic Patients: Radiography Versus Low-Dose Computed Tomography Evaluation

Abstract: Low-dose CT significantly showed larger number of normal PS results and diagnosed more severe PS lesions. As the determination of true sinus severity lesion impacts in asthma control, low-dose CT may replace PS plain X-ray and conventional CT to support better clinical decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Forty percent of CRS patients have been shown to have asthma, and sinus x-ray or computed tomography (CT) showed that 93% of those with asthma also had sinusitis. 2,3 Although several studies of CRS with asthma exhibited a significant improvement during short-term follow-up, the outcomes were worse than in patients without asthma. 4,5 Hzowever, the long-term effect of FESS-oriented multimodality treatment has not been sufficiently studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty percent of CRS patients have been shown to have asthma, and sinus x-ray or computed tomography (CT) showed that 93% of those with asthma also had sinusitis. 2,3 Although several studies of CRS with asthma exhibited a significant improvement during short-term follow-up, the outcomes were worse than in patients without asthma. 4,5 Hzowever, the long-term effect of FESS-oriented multimodality treatment has not been sufficiently studied.…”
Section: Introductionmentioning
confidence: 99%
“…Coexistence of asthma and rhinosinusitis has been noted in the medical literature for centuries. Forty percent of CRS patients have been shown to have asthma, and sinus x‐ray or computed tomography (CT) showed that 93% of those with asthma also had sinusitis . Although several studies of CRS with asthma exhibited a significant improvement during short‐term follow‐up, the outcomes were worse than in patients without asthma .…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective study by Seybt et al [5] has supported the concept of "one airway one disease" or "united airways." A cross-sectional study by Stelmach et al [6] has supported the theory of airway anatomical abnormalities, a link for the coexistence.…”
Section: Introductionmentioning
confidence: 87%
“…If any one of the findings that included mucosal thickening, opacity, and air-fluid level was observed in the PNS x-ray, the subject was considered as having comorbid sinusitis [10]. …”
Section: Methodsmentioning
confidence: 99%